The role of higher education institutions in sustainability initiatives at the local level. (1st October 2019) - Leal Filho, Walter; Vargas, Valeria Ruiz; Salvia, Amanda Lange; Brandli, Luciana Londero; Pallant, Eric; Klavins, Maris; Ray, Subhasis; Moggi, Sara; Maruna, Marija; Conticelli, Elisa; Ayanore, Martin Amogre; Radovic, Vesela; et al.
Abstract: Universities are central players and important economic actors in many regions, and many of them are, in general, nationally and internationally active in respect of matters related to sustainable development. But there is a paucity of research which examines their contributions towards sustainability efforts at the local level, i.e. in the places they are situated. This paper addresses this need, by reporting on a qualitative study deploying a Matrix, which allows an analysis and reporting of regional sustainable development initiatives of a set of 22 universities in industrialised and developing countries. Recommendations to enhance their role are provided, including the importance of pursuing partnerships and joint initiatives, understanding the need of local communities, and making their know-how more widely available. The scientific value of this research is related to the understanding of how the interaction between universities and local communities happens and by shedding light to this topic, it supports universities to improve their own actions. Its implications are two-fold: it demonstrates the potential of universities as local players and outlines the range of activities they may engage with, and which may allow them to act as pillars to local sustainability initiatives. Highlights: Universities are central players and important economic actors in many regions. Their contributions towards sustainability efforts at the local level may be substantial. An analysis and reporting of regional sustainable development initiatives shows some deficiencies. Understanding the potential role that universities can play on sustainability could help address global challenges.